1985
DOI: 10.1159/000199227
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Motility after Jejunal and Heal Resection: Electromyographic Study in Rats

Abstract: The aim of this work was to compare the effects of massive jejunal and ileal resections on intestinal motility using an electromyographic technique. Male Wistar rats were used: in the first group a massive jejunal resection was performed, conserving a 7-cm segment after the ligament of Treitz; the rats of the second group underwent an ileal resection, preserving 7 cm of the terminal ileum. Motility was studied at the 10th and 30th postoperative days by means of electrodes implanted throughout the remaining bow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1988
1988
1996
1996

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Intestinal motility after massive bowel resection has mainly been analyzed by absorption studies and the transit time demonstrated with radiopaque medium (6‐9). The somewhat limited studies of intestinal motility by myoelectric activity measurement (16,17) have not clarified the progressive postoperative changes of motility in conscious humans or experimental animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intestinal motility after massive bowel resection has mainly been analyzed by absorption studies and the transit time demonstrated with radiopaque medium (6‐9). The somewhat limited studies of intestinal motility by myoelectric activity measurement (16,17) have not clarified the progressive postoperative changes of motility in conscious humans or experimental animals.…”
Section: Discussionmentioning
confidence: 99%
“…Gut absorption, and hormonal and morphologic changes after MSBR have been studied, and bowel motility has been measured by barium meals to evaluate postoperative bowel function (6‐15). However, reports of intestinal motility after MSBR using myoelectric or strain gauge transducers have been limited (16,17), and continuous recording in conscious dogs is rare (17).…”
mentioning
confidence: 99%
“…Many investigators have confirmed the development of anatomical and functional adaptations (Grey & Morin, 1985;Hazel et al 1986;Wilson et al 1986;Kwan et al 1987) in the remaining segment. Experiments in laboratory animals have tried to enhance this response by varying the amount of bowel removed (Hanson et al 1977a), the site of resection (Antonson & Vanderhoof, 1982;Wittmann et al 1985), the postoperative time interval (Hanson et al 19773) or the diet (Biasco et al 1984;Ford et al 1985). In humans the management of these factors is limited and depends on the patient's state (Devine & Kelly, 1989).…”
mentioning
confidence: 99%